New strategy toward dioxin risk reduction for local residents surrounding severe dioxin hotspots in Vietnam - Vu-Anh Le (Global Health Action, 2013)
Background: A public health intervention program with active involvement of local related stakeholders was piloted in the Bien Hoa dioxin hotspot (2007–2009), and then expanded to the Da Nang dioxin hotspot in Vietnam (2009–2011). It aimed to reduce the risk of dioxin exposure of local residents through foods. This article presents the results of the intervention in Da Nang. Methodology: To assess the results of this intervention program, pre- and post-intervention knowledge, attitude, and practice (KAP) surveys were implemented in 400 households, randomly selected from four wards surrounding the Da Nang Airbase in 2009 and 2011, respectively. Results: After the intervention, the knowledge on the existence of dioxin in food, dioxin exposure pathways, potential high-risk foods, and preventive measures significantly increased (P<0.05). Ninety-eight percent were willing to follow advice on preventing dioxin exposure. Practices to reduce the risk of dioxin exposure also significantly improved (P<0.05). After intervention, 60.4% of households undertook exposure preventive measures, significantly higher than that of the pre-intervention survey (39.6%; χ2=40.15, P<0.001). High-risk foods had quite low rates of daily consumption (from 0 to 2.5%) and were significantly reduced (P<0.05). Conclusions: This is seen as an effective intervention strategy toward reducing the risk of human exposure to dioxin at dioxin hotspots. While greater efforts are needed for remediating dioxin-polluted areas inside airbases, there is also evidence to suggest that, during the past four decades, pollution has expanded to the surrounding areas. For this reason, this model should be quickly expanded to the remaining dioxin hotspots in Vietnam to further reduce the exposure risks in other areas.